Design leadership ignited elevating design at scale - Eric Quint, Gerda Gemser, Giulia Calabretta (Stanford, California Stanford Business Books, an Imprint of Stanford University Press, 2022)
"Transformational design leadership requires a leader who, rather than designing products, designs the design function, establishing a thriving environment for the creative team. It also requires a leader who helps to design the organization, making design a strategic capability that advances innovation and enhances customer experiences. To examine the foundations of strong design leadership, the authors performed extensive in-depth interviews with design leaders working for Fortune 500 organizations across industries and geographies. Based on these insights, the book takes the position that a core challenge to successful design leadership is the ability to effectively balance long-term goals and short-term outcomes that can be contradictory in nature. This book provides insights and guidelines that will help design and business leaders recognize these often contradictory challenges and leverage them to the benefit of both the design function and the organization at large. Through a combination of practitioner experience and empirical research, the authors demonstrate how design can be used as a strategic capability to advance innovation and enhance customer experience"-- Provided by publisher.
Includes bibliographical references (pages 203-216) and index.
Keywords: Leadership